UJICOBA MODUL PENYULUHAN TENTANG PENCEGAHAN KECELAKAAN RUMAH TANGGA PADA PENDUDUK PRA USIA LANJUT DAN USIA LANJUT DI KABUPATEN SLEMAN - Notosiswoyo, Mulyono; Supardi, Sudibyo (Media Penelitian dan Pengembangan Kesehatan, 2008)
Household accident occupied the second sequence after traffic accident. On that account we need to give counseling about household accident prevention, especially to age group with high risk to suffer from the accident. A counseling module has to be developed and tried in order to increase the knowledge about prevention of household accident of old resident. A quasi experiment study has been carried out in 2 sub district in Sleman District. Responders are old resident who have 56 year old or more. A sample of 160 as the counseling group and 160 as the control group was taken by multistage random sampling method based on RT and R W. Data were collected using questionnaire before and 2 months after counseling and analyzed with Chi-Square test and t-test. Result of the study shows that (1) counseling by using module can improve score knowledge of old people about prevention of household accident significantly to 40,3%, and (2) Module of household accident prevention can be used for the counseling of the old age groups.   Keyword: household accident, counseling, old age resident.